Pengaruh Pengawasan dan Fasilitas terhadap Kinerja Penyuluh Dinas Pertanian Kabupaten Labuhanbatu Utara yang Dimoderasi dengan Motivasi - Darma Aditya, Jufrizen, Hazmanan Khair (Pusdikra Publishing, 2021)
This study aims to determine the effect of supervision and facilities on the performance of the instructor and to determine the motivation in moderating the effect of supervision and facilities on the performance of the extension worker at the North Labuhanbatu Regency Agricultural Office. “This study uses a causal associative method with a quantitative descriptive approach to explain the causal relationship and influence between variables through hypothesis testing. The results showed that the effect of supervision and facilities on the performance of the agricultural extension workers in North Labuhanbatu Regency based on the indicators were as follows: First, there was a positive and significant influence between supervision on the performance of the extension workers, which means that if the supervision improves, the performance of the instructor will automatically increase as well. Second, there is a positive and significant effect between the facilities on the performance of the instructor, which means that if the facility increases, the performance of the instructor will improve. Third, motivation does not moderate the effect of supervision on the performance of the instructor. Fourth, motivation does not moderate the influence of facilities on the performance of the instructor. Directly motivation has a positive and significant effect on the performance of the instructor. It is hoped that the Department of Agriculture of North Labuhanbatu Regency will improve existing supervision and increase the provision of facilities for extension workers to improve their performance.